A new methodology to analyse and optimize territorial compensations of solar radiation intermittency: A case study in Corsica Island (France). (February 2022) - Haurant, P.; Muselli, M.; Gaillard, L.; Oberti, P.
Abstract: Territorial compensations of variability are a lever for smoothing the global photovoltaic production. They may allow a higher penetration rate of photovoltaic production in an energy mix, especially for non-interconnected islands. The aim of this paper is to analyse and optimize the smoothing effects of solar resource on a territory. In that view a novel typological classification-based methodology is proposed: intervals from highly intermittent episodes to ones with few fluctuations are discriminated. Then, the potential for compensation is demonstrated through the transformation from classes of high to low variability when summing solar radiation over several sites instead of one alone. The methodology is applied to Corsica. Solar radiation measured at 1 Hz on 8 sites which criss-crosses the island, when summed, demonstrates a reduction in the set of most intense variations compared to individual basis: they represent 5.5%–15.5% of the studied period for the sites taken individually against only 1.7% for the cumulated radiation. Optimization of the territorial compensation strategy leads to a near-disappearance of intense variations, with this class representing only 0.13% of the period. Finally, the optimized dispersion map of solar capacities results from this optimization.